2007
DOI: 10.1111/j.1364-3703.2007.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Host‐specific effect of P1 exchange between two potyviruses

Abstract: The potyviruses Plum pox virus (PPV) and Tobacco vein mottling virus (TVMV) have distinct host ranges and induce different symptoms in their common herbaceous hosts. To test the relevance of the P1 protein in host compatibility and pathogenicity, hybrid viruses were constructed in which the P1 coding sequence of PPV was completely or partially replaced by the corresponding sequences from TVMV. Infections induced by these chimeric viruses revealed that the TVMV P1 and a PPV/TVMV hybrid P1 proteins are functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…In comparison to a number of viruses in the family Potyviridae studied previously (reviewed by García-Arenal et al, 2001), SPMMV exhibited relatively high nucleotide diversity in the P1 region (Adams et al, 2005b). Data of previous studies suggest that P1 may be crucial for host adaptation in potyviruses (Shi et al, 2007;Salvador et al, 2008a). P1 proteins of potyviruses such as turnip mosaic virus and potato virus Y (PVY) have the largest v values among the mature viral proteins (at the population level), (Colinet et al, 1998) and E/P (Mukasa et al, 2003b) (broken arrows) are also shown.…”
Section: Discussionmentioning
confidence: 85%
“…In comparison to a number of viruses in the family Potyviridae studied previously (reviewed by García-Arenal et al, 2001), SPMMV exhibited relatively high nucleotide diversity in the P1 region (Adams et al, 2005b). Data of previous studies suggest that P1 may be crucial for host adaptation in potyviruses (Shi et al, 2007;Salvador et al, 2008a). P1 proteins of potyviruses such as turnip mosaic virus and potato virus Y (PVY) have the largest v values among the mature viral proteins (at the population level), (Colinet et al, 1998) and E/P (Mukasa et al, 2003b) (broken arrows) are also shown.…”
Section: Discussionmentioning
confidence: 85%
“…At least 36 recombination events were found between PRSV-P India and 11 other PRSV genomes from the rest of the world. The textured boxes are recombination hotspots assessed by the recombination detection program GeneConv range determination is also reported for Plum pox virus (PPV) and Tobacco vein mottling virus (TVMV) (Salvador et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, there are those trying to solve the real function of P1 protease in several potyviruses: Plum pox virus (PPV) (Salvador et al 2008), Tobacco vein mottling virus (TVMV) (Brantley and Hunt 1993;Klein et al 1994;Salvador et al 2008), Cucumber vein yellowing virus (CVYV) (Valli et al 2006(Valli et al , 2008, Soybean mosaic virus (SMV) (Gagarinova et al…”
Section: Potyviral P1 Protein: Function and Genetic Diversitymentioning
confidence: 99%